Fatherlessness and Children’s Rights: A Case Study from Bandar Baru District, Pidie Jaya Regency - Marcela Zalianti; Bukhari Ali; Gamal Achyar (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
The phenomenon of fatherlessness, or the absence of a father in a child's life, is increasingly common in society, whether due to death, divorce, or factors of residence or domicile. This study aims to analyze the impact of fatherlessness on the fulfillment of children's rights from an Islamic family law perspective, with a case study in Bandar Baru District, Pidie Jaya Regency. This study uses a qualitative approach with a field study method through in-depth interviews conducted with three children affected by fatherlessness and statements from their respective mothers, usually the absence of a father has a significant impact on the emotional, psychological, social conditions and rights of children. The results of the study indicate that in one case the absence of a father has a significant impact on the emotional, psychological, and social conditions of the child. In one case, the right to material support is fulfilled because the father works in Malaysia, but the right to affection and direct care is not fulfilled, resulting in symptoms of emotional instability and social envy. In another case, the father is not only emotionally absent but also neglects to provide support, resulting in a complete violation of children's rights according to Islamic family law. The perspective of fiqh munakahat emphasizes that the father has obligations to provide support, care (hadhanah), protection, and education for children. When these obligations are not fulfilled, children's rights are neglected, both physically and spiritually. This research concludes that the phenomenon of fatherlessness is not simply a social issue, but rather a legal and sharia-compliant issue that has serious implications for the protection of children's rights.